Multilevel inverter for standalone application with selective harmonic elimination - Goh, H. H.; Ling, C. W.; Chua, Q. S.; Goh, K. C.; Lee, S. S. (2016 International Symposium on Industrial Electronics (INDEL), 2016)
Renewable energy demand increases due to environmentally friendly. Power electronics development enhance the power quality produced. Standalone application multilevel inverter can help in improve rural area which is no electrified. For a multilevel inverter, the output required low total harmonics distortion and voltage boosting character. However, the conventional multilevel inverter are high distortion with high switching frequency. This paper is presenting multilevel inverter with selective harmonics elimination on reduce total harmonics distortion (THD) apply in standalone concept. 9-level cascaded H-bridge multilevel inverter is applied with optimize harmonics stepped waveform (OSHW) to compare performance with sinusoidal pulse width modulation (SPWM). In OSHW, selective harmonics elimination is used to reduce the low harmonics component which is 3 rd , 5 th and 7 th harmonics. Genetic algorithm are applied to solve the non-linear equation on solving the best switching angle. The result show OHSW have lower THD then SPWM. Meanwhile OHSW eliminated low harmonics component by the aid of genetic algorithm which exist due to the low switching frequency.